Foundations of augmented cognition. advancing human performance and decision-making through adaptive systems : 8th International Conference, AC 2014, Held as Part of HCI International 2014, Heraklion, Crete, Greece, June 22-27, 2014. Proceedings - Fidopiastis, Cali M.; Schmorrow, Dylan D. (Lecture Notes in Computer Science, 2014)
This book constitutes the proceedings of the 8th International Conference on the Foundations of Augmented Cognition, AC 2014, held as part of HCI International 2014 which took place in Heraklion, Crete, Greece, in June 2014 and incorporated 14 conferences which similar thematic areas. HCII 2014 received a total of 4766 submissions, of which 1476 papers and 220 posters were accepted for publication after a careful reviewing process. These papers address the latest research and development efforts and highlight the human aspects of design and use of computing systems. The papers thoroughly cover the entire field of Human-Computer Interaction, addressing major advances in knowledge and effective use of computers in a variety of application areas. The 34 papers presented in the AC 2014 proceedings are organized in topical sections named: emotional and cognitive issues in augmented cognition; machine learning for augmented cognition; augmented cognition for learning and training and augmented cognition for health and rehabilitation.